Beta-Lactam/Beta-Lactamase Inhibitor Therapy for Potential AmpC-Producing Organisms: A Systematic Review and Meta-Analysis. (23rd May 2019) - Cheng, Matthew P; Lee, Robyn S; Cheng, Alexandre P; De L'étoile-Morel, Samuel; Demir, Koray; Yansouni, Cedric P; Harris, Patrick; McDonald, Emily G; Lee, Todd C
Abstract: The optimal treatment for potential AmpC-producing Enterobacteriaceae, including Serratia, Providencia, Citrobacter, Enterobacter, and Morganella species, remains unknown. An updated systematic review and meta-analysis of studies comparing beta-lactam/beta-lactamase inhibitors with carbapenems in the treatment of bloodstream infections with these pathogens found no significant difference in 30-day mortality (OR, 1.13; 95% CI, 0.58 – 2.20). Abstract : The optimal treatment of bloodstream infections caused by potential AmpC-producing organisms is unsettled. A systematic review with meta-analysis found no significant difference in 30-day mortality in patients who were treated with beta-lactam/beta-lactamase inhibitors compared with carbapenems.